The Role of Interactive Technology in Enhancing Student Engagement in Mathematics - Bilqis, Ariendija Aisyah Shinta; Astuti, Wiwin; Hardi (Jurnal Pendidikan Matematika, 2025)
This study aims to analyse the use of interactive technology in mathematics learning to enhance student engagement. A descriptive qualitative approach was employed, involving six tenth-grade students from a senior high school in Surakarta. Data were collected through in-depth interviews, participatory observations, and documentation, and they were analysed using the Miles and Huberman interactive model. The findings indicate that the use of interactive technologies such as Quizizz, smartphones, and projectors contributes to increased student motivation, active participation, and a better understanding of abstract mathematical concepts. Features, including real-time feedback, material visualisation, and gamification, were found to be effective in creating an engaging and interactive learning environment. Furthermore, technology facilitates two-way communication between teachers and students and fosters students’ confidence to ask questions. However, the study also identified several challenges, including limited internet access, insufficient availability of devices, and teachers’ readiness to manage technological tools. Therefore, the integration of technology in mathematics learning requires adequate infrastructure, proper training for educators, and continuous supervision to ensure its optimal and equitable implementation. This study is expected to contribute to the development of effective, technology-based learning strategies to improve the quality of mathematics education in schools.